2021
DOI: 10.1590/2179-8087-floram-2021-0060
|View full text |Cite
|
Sign up to set email alerts
|

Studying Phytochemical Features of Three Asteraceae Herbs Growing Wild in Kazakhstan

Abstract: This study aimed to evaluate the phytochemical features of medicinal species of the Asteraceae family, their mineral elements, antioxidants, vitamins, and amino acids. The species studied included common yarrow (Achillea millefolium L.), common chicory (Cichorium intybus L.), and German chamomile (Chamomilla recutita (L.) Rauschert) collected in the Ile Alatau Mountain (Trans-Ili Alatau), Kazakhstan. The plants were harvested in July 2019-July 2020 during their flowering. The article's scientific novelty lies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Based on the results in previous studies the Asteraceae family (C. intybus L., Ch. Recutita L. and A. millefolium L. flowers) accumulates 13 free amino acids such as arginine, lysine, tyrosine, phenylalanine, histidine, leucine, isoleucine, methionine, valine, proline, threonine, serine, alanine and glycine [17]. Comparing free amino acids identificated in Cirsium vulgare, methionine, histidine and cystine were not detected.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results in previous studies the Asteraceae family (C. intybus L., Ch. Recutita L. and A. millefolium L. flowers) accumulates 13 free amino acids such as arginine, lysine, tyrosine, phenylalanine, histidine, leucine, isoleucine, methionine, valine, proline, threonine, serine, alanine and glycine [17]. Comparing free amino acids identificated in Cirsium vulgare, methionine, histidine and cystine were not detected.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, it should also be noted that some vegetables such as lettuce, and chrysanthemum, although belonging to the daisy family, it is close to the cruciferous family and also gives similar drug interactions for VKAs anticoagulants. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…As a result of studies on some Asteraceae family members, Achillea millefolium L. Zn: 2.487±0.029 mg/100 gr; Cu: 0.161±0.019 mg/100 g; Cichorium intybus L. Cu: 0.140±0.016 mg/100 g; Zn: 2.996±0.034 mg/100 g; Chamomilla recutita (L.) Rausch. Zn: 2.440±0.028 mg/100 g; Cu: 0.343±0.039 mg/100 g (Ashirova et al, 2021). The literature review about some other parameters that are the subject of our study is as follows; Baydar and Erdal (2004) examined the leaf Fe content of İzmir thyme and reported that they measured values in the range of 47.25-97.50 ppm, Meraler (2010) looked at the leaf Mn content of mahlep plant and determined the lowest as 8 ppm and the highest as 36 ppm.…”
Section: Determination Of Plant Nutrient Content Of Speciesmentioning
confidence: 97%